BETWEEN LAW AND LANGUAGE: MISTRANSLATION IN LOAN AGREEMENTS - Taufik Nur Hidayat; Supriatnoko; Nur Hasyim (Epigram, 2025)
Legal translation in financial technology (fintech) contracts demands high precision to preserve faithfulness, accuracy, consumer protection, and institutional integrity. This study investigates mistranslations in the English version of the Shopee Pinjam loan agreement, focusing on functional, lexical, and cultural distortions. Employing a qualitative descriptive approach, the research compares the Indonesian source text with its English counterpart to identify translation errors. A total of 72 mistranslation cases were found: functional (41.7%), lexical (38.9%), and cultural (19.4%). These findings demonstrate that mistranslation in fintech loan agreements not only compromises legal clarity but also risks consumer misinterpretation of obligations and rights. The study contributes theoretically by extending Newmark’s typology of mistranslation into a real-world fintech context and practically by highlighting the need for domain-specific competence among translators. It recommends the development of standardized glossaries, regulatory oversight, and collaboration between linguists and legal practitioners to safeguard translation quality in consumer-facing financial contracts.